The Role of Balian in the Island of Gods - Fahyan, Nadila Pradana; Farhah, Eva (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2024)
This study reveals the role of Balian in preserving traditional medicine as well as balancing the culture and mental health of the people on the Island of the Gods. This research was designed using a qualitative approach (medical ethnography). Informants were Hindu priests (Pemangku), local health workers and traditional medical experts (Balian). The research location was conducted in Balinese historical places that are believed to be qualified as a place to conduct traditional healing practices by a Balian, such as Pura (Pure), Holy Purifier (Tirta) and Beaches in Bali. The results show that the sickness and health of the Balinese ethnic soul refers to the concept of balancing the system elements in the body with cultural influences in the environment. Ethnic Balinese believe in the concept of Tri Hita Karana, which is the balance between Sang Hyang Widhi (God), Buana Agung (Universe) and Buana Alit (Human). If a person's physical or spiritual condition experiences an imbalance of these three things, then health is disturbed. In looking at the etiology of mental illness, they more than fully consider the abstract (non-physical) type of illness. The implication is that they seek Balian treatment as a primary option.